Anisotropic chitosan hemostatic aerogel and preparation method thereof

By using the preparation method of anisotropic chitosan hemostatic aerogel, using gamma irradiation and freeze-drying to form a fish bone-like structure, the problem of existing hemostatic materials being susceptible to infection and toxic crosslinking agents is solved, and the problem of existing hemostatic materials being easily infected and toxic crosslinking agents is realized. Combination of efficient hemostatic and antibacterial properties.

CN119455065APending Publication Date: 2025-02-18SICHUAN INST OF ATOMIC ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411646918.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing hemostatic materials have a long hemostatic time, easy infection, easy adhesion to wounds, and difficult to change the medicine. The traditional crosslinking agent is toxic, which limits its application in the field of biomedical medicine.

Method used

The preparation method of anisotropic chitosan hemostatic aerogel is adopted. By dissolving chitosan in acetic acid solution, mixing it with components such as polyvinyl alcohol and sanshalaldehyde, and then gamma irradiation and freeze-drying, it forms a fish bone. aerogel in shape. This method utilizes radiation crosslinking, avoids the use of toxic crosslinking agents, and provides antibacterial properties through MgO nanoparticles.

Benefits of technology

The prepared anisotropic chitosan hemostatic aerogel has high longitudinal mechanical strength and low transverse modulus, which is suitable for non-compressive hemostatic, and has excellent antibacterial properties, and is suitable for biomedical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455065A_ABST
    Figure CN119455065A_ABST
Patent Text Reader

Abstract

The invention discloses anisotropic chitosan hemostatic aerogel and a preparation method thereof, and relates to the technical field of biomedical materials.The preparation method comprises the following steps that chitosan is dissolved in an acetic acid solution, and a chitosan solution is obtained; dissolving polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol solution; the preparation method comprises the following steps: mixing ethanol with deionized water, adding salvia aldehyde, and dissolving to obtain a salvia aldehyde solution; adding magnesium salt and a stabilizer into the acetic acid-sodium acetate buffer solution, and uniformly mixing to obtain a magnesium salt solution; the preparation method comprises the following steps: mixing a chitosan solution, a polyvinyl alcohol solution and a salvia aldehyde solution, adding a magnesium salt solution and a cross-linking agent, carrying out ultrasonic treatment, pouring into a mold, sealing, and carrying out irradiation and freeze drying to obtain the anisotropic chitosan hemostatic aerogel. The invention discloses the anisotropic chitosan hemostatic aerogel prepared by the method. The aerogel has an obvious fishbone-shaped structure, is high in longitudinal mechanical strength and low in transverse modulus, has an antibacterial effect, and has a relatively high application value in the aspect of non-compression hemostasis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to an anisotropic chitosan hemostatic aerogel and a preparation method thereof. Background Art

[0002] Existing hemostatic materials such as hemostatic bandages have disadvantages such as long hemostatic time, easy infection, easy adhesion to wounds, and difficulty in changing dressings, which affect their hemostatic effects. Therefore, it is of great significance to develop a hemostatic material that is fast in hemostasis, low in cost, easy to operate, easy to store, and has good biocompatibility. Aerogel materials, as the lowest density solid material, replace all the liquid in the gel pore structure with gas through supercritical or freeze drying, while avoiding the damage to the pore structure caused by surface tension and capillary action, to obtain a three-dimensional nano-network structure with high specific surface area, high porosity and extremely low density.

[0003] Chitosan (CS) is a natural polymer biodegradable material. It is the only positively charged alkaline polysaccharide in nature. It can attract negatively charged blood cells, thereby inducing platelet aggregation, and stimulating platelets to release coagulation factors, promoting and accelerating blood coagulation. Chitosan forms various intramolecular and intermolecular hydrogen bonds through the interaction of hydroxyl, amino, and N-acetylamino groups distributed on the macromolecular chain. At the same time, it can react with other active groups to improve the functionality of the material. Polysaccharide gels such as chitosan are often chemically cross-linked using external chemical reagents, such as formaldehyde, glyoxal, glutaraldehyde, etc., which are often used to cross-link gels. These aldehyde groups easily form hemiacetal bonds with the hydroxyl groups of polysaccharides to form gels. This type of organic reagent is often toxic and has a long reaction time, which limits its application in the biomedical field. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an anisotropic chitosan hemostatic aerogel and a preparation method thereof. The aerogel has an obvious herringbone structure, high longitudinal mechanical strength and low transverse modulus, and has antibacterial effect, and has great application value in non-compression hemostasis.

[0005] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing anisotropic chitosan hemostatic aerogel is provided, comprising the following steps: (1) dissolving chitosan in acetic acid solution to obtain a chitosan solution; (2) dissolving polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol solution; (3) mixing ethanol and deionized water, adding danshen aldehyde to dissolve, and obtaining danshen aldehyde solution; (4) adding magnesium salt and stabilizer to acetic acid-sodium acetate buffer and mixing evenly to obtain a magnesium salt solution; (5) The chitosan solution obtained in step (1) is mixed with the polyvinyl alcohol solution obtained in step (2), and the danshen aldehyde solution obtained in step (3) is added and mixed evenly, and then the magnesium salt solution obtained in step (4) is added, and then a cross-linking agent is added and ultrasonically dispersed. After mixing evenly, the mixture is poured into a mold and sealed, and then subjected to gamma irradiation and freeze drying to obtain anisotropic chitosan hemostatic aerogel.

[0006] Furthermore, in step (1), the concentration of the acetic acid solution is 1-5 wt%; and the concentration of the chitosan solution is 2-5 wt%.

[0007] Furthermore, in step (2), the molecular weight of the polyvinyl alcohol is 10,000-30,000; and the concentration of the polyvinyl alcohol solution is 5-10 wt%.

[0008] Furthermore, in step (2), the mixture is dissolved by stirring at 80-100°C.

[0009] Furthermore, in step (3), the volume ratio of ethanol to deionized water is 1:3-5.

[0010] Furthermore, in step (3), the concentration of the danshen aldehyde solution is 0.1-0.5 mol / mL.

[0011] Furthermore, in step (4), the pH of the acetic acid-sodium acetate buffer solution is 5.5-6.5; the magnesium salt is magnesium sulfate or magnesium chloride; and the concentration of the magnesium salt solution is 0.5-1.5 mmol / mL.

[0012] Furthermore, in step (4), the stabilizer is polyvinyl alcohol or sodium dodecyl sulfate, and the amount of the stabilizer is 0.1-0.5 mg / L.

[0013] Furthermore, in step (5), the volume ratio of chitosan solution, polyvinyl alcohol solution, danshen aldehyde solution, magnesium salt solution and cross-linking agent is 1-3:0.5-1.5:0.5-1.5:0.5-1.5:0.5-1.5; the cross-linking agent is at least one of ferric chloride solution and aluminum chloride solution, and the concentration of the cross-linking agent is 1-5 mmol / mL.

[0014] Furthermore, in step (5), the dose of gamma irradiation is 5-30 kGy.

[0015] The beneficial effect of taking further technical solutions is that radiation technology is often used to prepare metal nanoparticles (Metal Nano Particles, MNPs), because the solvated electrons (e aqThe potentials of the free radicals (∙H) and hydrogen radicals (∙H) are -2.87 V and -2.3 V, respectively, which can effectively reduce metal ions in the solution to metal atoms, thereby forming metal nanoparticles in situ. Different from traditional methods, radiation reduction can obtain impurity-free, fully reduced and highly stable MNPs due to the high energy of the radiation and the absence of reducing agents. At the same time, by controlling the absorbed dose, reaction medium and stabilizer, MNPs of different particle sizes and morphologies can be synthesized. Therefore, it has obvious advantages in the synthesis of biomedical nanoparticles.

[0016] The invention also discloses anisotropic chitosan hemostatic aerogel prepared by the preparation method of the anisotropic chitosan hemostatic aerogel.

[0017] The present invention has the following beneficial effects: 1. The method of the present invention utilizes the hydroxyl group of danshen aldehyde to combine with iron ions or aluminum ions, and at the same time, the aldehyde group on danshen aldehyde reacts with the amino group of chitosan to generate an imine structure by Schiff base reaction, forming a primary network structure of chitosan cross-linked gel, and forming a secondary network structure by irradiating the cross-linked PVA system, constructing a gel system with a double network structure, and then using freeze-drying technology to prepare an aerogel material. The aerogel prepared by this method has an obvious fishbone-shaped (anisotropic) structure, and has obvious differences in longitudinal and transverse mechanical properties. The high longitudinal mechanical compression strength is conducive to the longitudinal support of the aerogel, while the low transverse modulus is conducive to the non-compressive hemostasis of the aerogel.

[0018] 2. While irradiating cross-linked PVA, Mg 2+ MgO nanoparticles were synthesized by in-situ deposition in the gel system. The adsorption of MgO nanoparticles on microorganisms and the ROS oxidative damage mechanism provide aerogels with excellent antibacterial properties. At the same time, studies have shown that magnesium ions have the effect of promoting angiogenesis and differentiation of bone marrow mesenchymal stem cells, and appropriate concentrations of magnesium ions are beneficial to the growth and differentiation of pro-cells and mesenchymal stem cells. MgO nanoparticles have neither a rapid degradation rate nor produce hydrogen in the body, so they can also be used as a source of Mg. 2+ Source.

[0019] 3. The method of the present invention controls the irradiation dose, irradiation medium and polyvinyl alcohol content, and can regulate the structure and mechanical properties of aerogel.

[0020] 4. The method of the present invention performs cross-linking by irradiation. Compared with other cross-linking methods, it does not require the addition of any additives, thus avoiding the introduction and residual problems of toxic cross-linking agents. The product can also be disinfected and sterilized during irradiation preparation, and the operation is convenient and simple, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1This is an electron microscope image of the anisotropic chitosan hemostatic aerogel of Example 1; Figure 2 This is an electron microscope image of MgO particles in the anisotropic chitosan hemostatic aerogel of Example 1; Figure 3 This is the EDS spectrum of the anisotropic chitosan hemostatic aerogel of Example 1; Figure 4 This is the stress-strain curve of anisotropic chitosan hemostatic aerogel. DETAILED DESCRIPTION

[0022] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0023] Example 1 An anisotropic chitosan hemostatic aerogel, the preparation method of which comprises the following steps: (1) Dissolving chitosan in 2wt% acetic acid solution to obtain a 3wt% chitosan solution; (2) stirring and dissolving polyvinyl alcohol with a molecular weight of 20,000 in deionized water at 90° C. to obtain an 8 wt % polyvinyl alcohol solution; (3) Mix ethanol and deionized water in a volume ratio of 1:4, add danshen aldehyde to dissolve, and obtain a 0.3 mol / mL danshen aldehyde solution; (4) Add magnesium chloride and 0.1-0.5 mg / L polyvinyl alcohol to pH 6 acetic acid-sodium acetate buffer and mix well to obtain a 1 mmol / mL magnesium salt solution; (5) Mix 2 mL of the chitosan solution obtained in step (1) with 1 mL of the polyvinyl alcohol solution obtained in step (2), add 1 mL of the danshen aldehyde solution obtained in step (3) and mix evenly, then add 1 mL of the magnesium salt solution obtained in step (4), and then add 1 mL of a 3 mmol / mL ferric chloride solution for ultrasonic dispersion. After mixing evenly, pour into a mold and seal it. After 20 kGy gamma irradiation and freeze-drying, anisotropic chitosan hemostatic aerogel is obtained.

[0024] Example 2 An anisotropic chitosan hemostatic aerogel, the preparation method of which comprises the following steps: (1) Dissolving chitosan in 1wt% acetic acid solution to obtain 2wt% chitosan solution; (2) Dissolve polyvinyl alcohol with a molecular weight of 10,000 in deionized water at 90° C. by stirring to obtain a 5 wt % polyvinyl alcohol solution; (3) Mix ethanol and deionized water in a volume ratio of 1:3, add danshen aldehyde to dissolve, and obtain a 0.1 mol / mL danshen aldehyde solution; (4) Add magnesium chloride and 0.1 mg / L polyvinyl alcohol to pH 6 acetic acid-sodium acetate buffer and mix well to obtain a 0.5 mmol / mL magnesium salt solution; (5) 1 mL of the chitosan solution obtained in step (1) was mixed with 0.5 mL of the polyvinyl alcohol solution obtained in step (2), and 0.5 mL of the danshen aldehyde solution obtained in step (3) was added and mixed evenly. Then, 0.5 mL of the magnesium salt solution obtained in step (4) was added, and then 0.5 mL of 1 mmol / mL ferric chloride solution was added and ultrasonically dispersed. After mixing evenly, the mixture was poured into a mold and sealed. After 5 kGy gamma irradiation and freeze-drying, anisotropic chitosan hemostatic aerogel was obtained.

[0025] Example 3 An anisotropic chitosan hemostatic aerogel, the preparation method of which comprises the following steps: (1) Dissolving chitosan in 5wt% acetic acid solution to obtain a 5wt% chitosan solution; (2) Stir and dissolve polyvinyl alcohol with a molecular weight of 30,000 in deionized water at 90°C to obtain a 10 wt% polyvinyl alcohol solution; (3) Mix ethanol and deionized water in a volume ratio of 1:5, add danshen aldehyde to dissolve, and obtain a 0.5 mol / mL danshen aldehyde solution; (4) Add magnesium sulfate and 0.5 mg / L sodium dodecyl sulfate to the pH = 6 acetic acid-sodium acetate buffer and mix well to obtain a 1.5 mmol / mL magnesium salt solution; (5) 3 mL of the chitosan solution obtained in step (1) was mixed with 1.5 mL of the polyvinyl alcohol solution obtained in step (2), and 1.5 mL of the danshen aldehyde solution obtained in step (3) was added and mixed evenly. Then, 1.5 mL of the magnesium salt solution obtained in step (4) was added, and then 1.5 mL of 5 mmol / mL aluminum chloride solution was added for ultrasonic dispersion. After mixing evenly, the mixture was poured into a mold and sealed. After 30 kGy gamma irradiation and freeze-drying, anisotropic chitosan hemostatic aerogel was obtained.

[0026] Test Example 1 (1) The anisotropic chitosan hemostatic aerogel obtained in Example 1 was observed by scanning electron microscopy. The results are as follows: Figure 1 shown.

[0027] Depend on Figure 1It can be seen that the anisotropic chitosan hemostatic aerogel of the present invention has an obvious fishbone structure, indicating that it has mechanical anisotropy and has obvious differences in longitudinal and transverse mechanical properties. The high longitudinal mechanical compression strength is beneficial to the longitudinal support of the aerogel, while the low transverse modulus is beneficial to the non-compressive hemostasis of the aerogel.

[0028] (2) The electron microscope photo and energy spectrum of the MgO particles of the anisotropic chitosan hemostatic aerogel obtained in Example 1 are shown in Figure 2 and Figure 3 shown.

[0029] Depend on Figure 2 and Figure 3 It can be seen that the method of the present invention uses radiation to induce the in-situ generation of nano-MgO particles from magnesium salts, and the MgO particles are evenly dispersed in the aerogel system, avoiding the accumulation of inorganic particles to produce local inflammation, and giving the aerogel excellent antibacterial function.

[0030] Test Example 2 Referring to the preparation method in Example 1, 1 wt%, 1.5 wt% and 2 wt% chitosan solutions were used to prepare anisotropic chitosan hemostatic aerogels. The compression strain rates were set to 20%, 40%, 60% and 80%, and the mechanical properties of each aerogel were tested. The results are shown in Tables 1 and Figure 4 shown.

[0031] Table 1 Aerogel mechanical properties test results

[0032] From Table 1 and Figure 4 It can be seen that when the strain is 80%, each group of anisotropic chitosan hemostatic aerogels still exhibits high stress in the axial direction, which is beneficial to the supporting effect of the aerogel; while the stress in the radial direction is much smaller than that in the axial direction. The results show that the anisotropic chitosan hemostatic aerogel of the present invention has good mechanical anisotropy.

Claims

1. A method for preparing anisotropic chitosan hemostatic aerogel, characterized in that: The following steps are involved: (1) dissolving chitosan in acetic acid solution to obtain a chitosan solution; (2) dissolving polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol solution; (3) mixing ethanol and deionized water, adding danshen aldehyde to dissolve, and obtaining danshen aldehyde solution; (4) adding magnesium salt and stabilizer to acetic acid-sodium acetate buffer and mixing evenly to obtain a magnesium salt solution; (5) The chitosan solution obtained in step (1) is mixed with the polyvinyl alcohol solution obtained in step (2), and the danshen aldehyde solution obtained in step (3) is added and mixed evenly, and then the magnesium salt solution obtained in step (4) is added, and then a cross-linking agent is added and ultrasonically dispersed. After mixing evenly, the mixture is poured into a mold and sealed, and then subjected to gamma irradiation and freeze drying to obtain anisotropic chitosan hemostatic aerogel.

2. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (1), the concentration of the acetic acid solution is 1-5 wt%; the concentration of the chitosan solution is 2-5 wt%.

3. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (2), the molecular weight of the polyvinyl alcohol is 10000-30000; the concentration of the polyvinyl alcohol solution is 5-10wt%.

4. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (3), the volume ratio of ethanol to deionized water is 1:3-5.

5. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (3), the concentration of the danshen aldehyde solution is 0.1-0.5 mol / mL.

6. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (4), the pH of the acetic acid-sodium acetate buffer is 5.5-6.5; the magnesium salt is magnesium sulfate or magnesium chloride; and the concentration of the magnesium salt solution is 0.5-1.5 mmol / mL.

7. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (4), the stabilizer is polyvinyl alcohol or sodium dodecyl sulfate, and the amount of the stabilizer is 0.1-0.5 mg / L.

8. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (5), the volume ratio of the chitosan solution, polyvinyl alcohol solution, danshen aldehyde solution, magnesium salt solution and cross-linking agent is 1-3: 0.5-1.5: 0.5-1.5: 0.5-1.5: 0.5-1.5; the cross-linking agent is at least one of ferric chloride solution and aluminum chloride solution, and the concentration of the cross-linking agent is 1-5 mmol / mL.

9. The method for preparing the anisotropic chitosan hemostatic aerogel according to claim 1, characterized in that: In step (5), the dose of gamma irradiation is 5-30 kGy.

10. Anisotropic chitosan hemostatic aerogel prepared by the method for preparing anisotropic chitosan hemostatic aerogel according to any one of claims 1 to 9.